Respuesta :
Answer:
explicit formula: Un=-3*-4ⁿ⁻¹
Recursive Formula: U₆=-3*-4⁶⁻¹ = 3072
Step-by-step explanation:
Explicit formula:
Un=U₁*rⁿ⁻¹
U₁=First term
r=common ratio
Un=nth number of the sequence.
r=12/-3=-48/12=-4
Un=-3*-4ⁿ⁻¹
Recursive Formula for U₆
U₆=-3*-4⁶⁻¹
U₆=-3*-4⁵
U₆=-3*-1024
U₆=3072
Answer:
see below
Step-by-step explanation:
-3,12,-48,.........
the first term is [tex]a_{1}[/tex] =-3
The ratio is [tex]a_{2}[/tex]/[tex]a_{1}[/tex] = 12/-3 = -4
The recursive formula is
[tex]a_{n}[/tex]= r* [tex]a_{n-1}[/tex]
[tex]a_{n}[/tex]= -3 * [tex]a_{n-1}[/tex]
The explicit formula
[tex]a_{n}[/tex] = [tex]a_{1}[/tex] * r^ (n-1)
[tex]a_{n}[/tex] = -3 * -4^ (n-1)
To find the 6th term let n=6
[tex]a_{6}[/tex] = -3 * -4^ (6-1)
[tex]a_{6}[/tex] = -3 * -4^ (5)
[tex]a_{6}[/tex] = -3 * -1024 =3072